Transparency and electronic government: traditional census vs digital census Bolivia case - Vargas Díaz, César Daniel (2023)
This research work has the importance of proposing a digital census in the framework of electronic government, which allows governments to collect more statistical information, as well as to disseminate social, economic and political information towards greater transparency, both in demographic, economic and electoral statistical data for parliamentary seats, from the efficiency, effectiveness, economy and excellence, through the tools provided by the Information and Communication Technologies and especially the Internet, enhancing an electronic transparency of information via the Web that are of enormous scope to the citizen client. To this end, we propose a digital census or "e-census" for Bolivia with disclosure of information, revealing the levels of transparency of statistical information and democratic openness of public management.